MacroSwarm: A scala framework for swarm programming - Aguzzi, Gianluca; Viroli, Mirko (Science of computer programming, 2025)
Programming swarm behaviors is a challenging task, due to the need to express collective behaviors in terms of local interactions among simple agents. Even if several programming frameworks have been proposed, they are often based on low-level abstractions, which makes the development of swarm applications complex and error-prone. Thus, we present MacroSwarm, an aggregate programming framework for the development of swarm behaviors. With this framework, it is possible to define a large variety of swarm behaviors, starting from simple movements to more complex ones, such as aggregation, flocking, and collective decision-making. In this paper, we present the main features of the framework and some simple examples of its API usage.